mRNA-engineered T lymphocytes secreting bispecific T cell engagers with therapeutic potential in solid tumors - Zagorac, Ivana; Ramírez-Fernández, Ángel; Tapia-Galisteo, Antonio; Rubio-Pérez, Laura; Gómez-Rosel, Marina; Grau, Montserrat; Rodríguez-Peralto, José Luis; Álvarez-Vallina, Luis; Blanco, Belén (Frontiers in Immunology, 2025)
BackgroundIn the last decade, chimeric antigen receptor (CAR)-modified T cells have revolutionized the treatment of hematologic malignancies. However, antitumor responses in solid tumors remain poor, and the difficulty in finding truly tumor-specific target antigens leads to a high risk of on-target/off-tumor toxicity. Transient modification with mRNA is gaining momentum as an alternative approach to viral transduction in order to achieve a better safety profile. On the other hand, generation of T cells secreting bispecific T cell engagers (TCEs) has been reported to outperform the antitumor efficacy of T lymphocytes expressing membrane-anchored CARs, due to the ability of the soluble TCEs to recruit unmodified bystander T cells.MethodsWe have electroporated human primary T cells with in vitro transcribed mRNA encoding an anti-EGFR x anti-CD3 bispecific T cell engager. Such mRNA-modified T cells (STAREGFR-T cells) have been analyzed for anti-EGFR bispecific TCE secretion and for their ability to drive anti-tumor responses against EGFR-expressing cells, both in vitro and in vivo.ResultsSTAREGFR-T cells transiently secrete bispecific TCEs capable of redirecting T lymphocytes to exert tumor cell-specific killing in in vitro assays. Moreover, STAREGFR-T cells efficiently control tumor growth in in vivo xenograft models of solid malignancy.ConclusionsOur results strongly support mRNA-engineered TCE-secreting T cells as a promising therapeutic strategy for solid tumors.